Hip involvement in early rheumatoid arthritis. Issue 1 (January 1995) - Eberhardt, K; Fex, E; Johnsson, K; Geborek, P
Abstract : OBJECTIVE--To study early hip involvement in rheumatoid arthritis (RA) and to evaluate the usefulness of ultrasonography in the detection of hip joint synovitis in RA. METHODS--Study I: The number of hip joint replacements was recorded in a cohort of 113 patients with RA of at least five years disease duration followed from an early stage. Study II: Ultrasonography was evaluated as a method to identify hip joint synovitis in 76 patients with RA of shorter disease duration, by relating it to radiograms and clinical findings. RESULTS--Study I: Twenty one hip joint replacements were performed in 15 of the 113 patients. The median disease duration at the time of first arthroplasty was 48 (range 10-76) months; the annual incidence was approximately constant between two and six years. High disease activity at the start of the study was predictive of requirement for hip prosthesis. Study II: Hip ultrasonography was pathological in 13 of the 76 patients studied, bilaterally in nine. Hip joint synovitis could not be confirmed on clinical grounds only as seven of the patients with positive ultrasonographic findings were asymptomatic, and the remaining six patients had only mild symptoms of hip involvement. Also, six of the 63 patients with normal ultrasonography had mild symptoms. There was no difference regarding demographic, clinical, and laboratory findings in patients with and without hip synovitis. CONCLUSIONS--Early hip joint destruction giving symptoms mostly at a very late stage is frequent in RA. Ultrasonography rather than signs or symptoms could identify patients with hip joint involvement and provide a rationale for early treatment.